Análise tipológica e descrição arquivística: um olhar para a história da desapropriação de terras na construção do campus da UFSM - Gomes, Dione Calil (2013)
Academic archives preserve documents that are testimonies of the institutional memory, serving as support to the Administration and the teaching, research and extension activities. In the Universidade Federal de Santa Maria (UFSM), the Departamento de Arquivo Geral (DAG) is responsible for preserving the archivistic heritage of the university. Thus, it aims to develop initiatives to ensure the treatment and access to public information. In the indicated context, this research fits with the objective of describing the documents referred to the expropriation of demesnes which originated the first phase of the UFSM s campus construction. This group of documents integrates the estate of the university s realties that are maintained by the Departamento de Arquivo Geral. Those written files were constituted as of December, 1st, 1961, date of publication of the Decreto n. 267 (enactment), which stated, as public interest for expropriation, glebes destined to placement and installation of the Universidade Federal de Santa Maria, at that time. The paper is characterized as a descriptive research with a qualitative approach. The tools of data collect were direct observation and documental analysis. The theoretical principles of Diplomatic, Documental Typology and Typological Analysis grounded this study that enabled an archivistic description based on the Brazilian Standard Archival Description (NOBRADE). As result of the research, it is presented a catalog of the documents that were object of the study.